Identifikasi dan Intervensi ISPA Melalui Pengalaman Belajar Lapangan Di Dusun IV Desa Tuntungan II - Harahap, Reni Agustina; Siregar, Nazwa Syafira Irwani; Sihite, Rahel Navilia; Zulaila, Zulaila (Yayasan Jompa Research and Development, 2025)
This study aims to identify as well as intervene in public health problems through Field Learning Experience (PBL) activities in Dusun IV Tuntungan II Village, Deli Serdang Regency. The research method used a descriptive design with a qualitative approach. Primary data were collected through observation, in-depth interviews, and questionnaires, while secondary data were obtained from the village health profile and UPT Puskesmas Tuntungan Pancur Batu. Prioritization of health problems was carried out using the USG (Urgency, Seriousness, Growth) method which was then validated through hamlet meetings with the community and local leaders. The results showed that Acute Respiratory Tract Infection (ARI) was the top priority with the highest score, followed by hypertension. Risk factors for ARI include low community knowledge, the habit of burning garbage, housing conditions that do not meet health standards, and the lack of health promotion activities. The interventions implemented included counseling on ARI prevention, distribution of educational leaflets, training on waste processing into compost, mutual cooperation activities to clean the environment, and installation of signs committing residents to maintain cleanliness. The results of the intervention implementation showed an increase in community awareness about ARI prevention and behavior change towards a clean and healthy lifestyle. Thus, community participation-based interventions have proven to be effective in reducing the real factors of ARI.